Dissociation and its disorders: Competing models, future directions, and a way forward. (November 2019) - Lynn, Steven Jay; Maxwell, Reed; Merckelbach, Harald; Lilienfeld, Scott O.; Kloet, Dalena van Heugten-van der; Miskovic, Vladimir
Abstract: Dissociative experiences and symptoms have sparked intense scrutiny and debate for more than a century. Two perspectives, the trauma model (TM), which postulates a direct and potent causal link between trauma and dissociation, and the sociocognitive model (SCM), which emphasizes social and cognitive variables (e.g., fantasy-proneness, media influences, suggestibility, suggestion, cognitive failures), currently vie for support. The intensive focus on controversies has stymied progress in understanding dissociation as much, if not more, than it has inspired research that transcends a single perspective. We assess strengths and limitations of these two perspectives and contend that neither provides a complete account of dissociation symptoms, which occur in the presence of many disorders. We provide a novel, narrative review of the link between dissociation and dissociative disorders and sleep disruptions, hyperassociativity, set shifts, deficits in meta-consciousness, and impaired self-regulation. We suggest that these transtheoretical variables (a) play a role in disorders that covary extensively with dissociative disorders (i.e., borderline personality disorder, schizophrenia spectrum disorders) and (b) provide the basis for overlapping foci of interests and potential collaborations among proponents of competing theoretical camps. Finally, we discuss limitations in knowledge and unresolved issues for future workers in the field to pursue. Highlights: Assesses strengths/weaknesses of sociocognitive and posttraumatic dissociation models Provides systematic narrative review of variables not considered by either perspective Reviews hyperassociativity, set shifts, emotion regulation, sleep, meta-consciousness Variables play role in dissociation, schizophrenia, borderline personality disorders. Discusses limitations in knowledge, unresolved issues